Transfusion in orthopaedic surgery: a retrospective multicentre cohort study. (1st October 2021) - Blankstein, Anna R.; Houston, Brett L.; Fergusson, Dean A.; Houston, Donald S.; Rimmer, Emily; Bohm, Eric; Aziz, Mina; Garland, Allan; Doucette, Steve; Balshaw, Robert; Turgeon, Alexis; Zarychanski, Ryan
Abstract : Aims: Orthopaedic surgeries are complex, frequently performed procedures associated with significant haemorrhage and perioperative blood transfusion. Given refinements in surgical techniques and changes to transfusion practices, we aim to describe contemporary transfusion practices in orthopaedic surgery in order to inform perioperative planning and blood banking requirements. Methods: We performed a retrospective cohort study of adult patients who underwent orthopaedic surgery at four Canadian hospitals between 2014 and 2016. We studied all patients admitted to hospital for nonarthroscopic joint surgeries, amputations, and fracture surgeries. For each surgery and surgical subgroup, we characterized the proportion of patients who received red blood cell (RBC) transfusion, the mean/median number of RBC units transfused, and exposure to platelets and plasma. Results: Of the 14, 584 included patients, the most commonly performed surgeries were knee arthroplasty (24.8%), hip arthroplasty (24.6%), and hip fracture surgery (17.4%). A total of 10.3% of patients received RBC transfusion; the proportion of patients receiving RBC transfusions varied widely based on the surgical subgroup (0.0% to 33.1%). Primary knee arthroplasty and hip arthroplasty, the two most common surgeries, were associated with in-hospital transfusion frequencies of 2.8% and 4.5%, respectively. RBC transfusion occurred in 25.0% of hip fracture surgeries, accounting for the greatest total number of RBC units transfused in our cohort (38.0% of all transfused RBC units). Platelet and plasma transfusions were uncommon. Conclusion: Orthopaedic surgeries were associated with variable rates of transfusion. The rate of RBC transfusion is highly dependent on the surgery type. Identifying surgeries with the highest transfusion rates, and further evaluation of factors that contribute to transfusion in identified at-risk populations, can serve to inform perioperative planning and blood bank requirements, and facilitate pre-emptive transfusion mitigation strategies. Cite this article: Bone Jt Open  2021;2(10):850–857.